Percaya Diri, Body Image dan Kecenderungan Anorexia Nervosa Pada Remaja Putri - Ratnawati, Vivi (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. This study aims to find whether there is a relationship between self-confidence and body image with the trend of anorexia nervosa in adolescent princess. Subjects of the study were 120 student of SMK Negeri 2 Kediri. Three scales were used to collect data and then this data were analysed by multiple regression with stepwise method. The results showed self-confidence and body image together give to the tendency of anorexia nervosa. Based on the results the hypothesis proposed in this study can be accepted, that there is a negative relationship between self-confidence and body image with the trend of anorexia nervosa. The effective contribution of each individual predictor, self-confidence to have a role that is 9,1% while body image that is 26,1%.Keywords : Self-confidence, body image, anorexia nervosa